(untitled) (Journal of Economic Research & Business Administration, 2020)
This article discusses the important issues in the selection and management of the investment portfolio, which are used. In order to achieve the established level of profitability and reduce the level of risk, the basic principles of well-known economists and investment rules are presented. Discusses the various factors used to evaluate the effectiveness of portfolio management of financial investments. It was noted that profitability and risk are the main parameters for the evaluation of any investment, including the investment portfolio. There is always a trade between risk and return. Therefore, the combination of assets affects the quality of the portfolio. The selective model of G. Markowitz, who is the founder of the portfolio, is also analyzed. The model is designed to assess the risk and return of the portfolio and calculate their correlation and covariance.Among the analyzed factors-the coefficient of the square, Sortino ratio, omega ratio, beta coefficient, coefficient alpha, coefficient of VaR and others. Advantages of application of any coefficient were defined. It was stressed that the results of the study needed to be informed about the portfolio using each factor and considered in an integrated manner. In improving the efficiency of the investment portfolio, the importance of investing in index funds was noted. In addition to the provided coefficients, it is necessary to pay attention to the investor’s own goals, as well as to other indicators of the funds‘ activities. Sovereign wealth funds in the world today use different approaches to risk assessment and the formation of their investment portfolios-one distributes its funds in favor of the most risky assets, others adhere to conservative strategies. The management of such funds should be based on a carefully considered investment strategy.The results of the research are used in the framework of the correct formation of the investment portfolio and management.